The additive free microwave hydrolysis of lignocellulosic biomass for fermentation to high value products. (10th October 2018) - Fan, Jiajun; Santomauro, Fabio; Budarin, Vitaliy L.; Whiffin, Fraeya; Abeln, Felix; Chantasuban, Tanakorn; Gore-Lloyd, Deborah; Henk, Daniel; Scott, Roderick J.; Clark, James; Chuck, Christopher J.
Abstract: Current biorefineries are predominantly based around single feedstock sources, extensively hydrolysed using multiple unit operations. The hydrolysate is generally converted to a single product by one of a few well-characterised organisms. Here, we report on a new approach to the biorefinery, combining a rapid, microwave heated, one-step depolymerisation process, with a yeast, Metschnikowia pulcherrima which is able to metabolise an array of oligo- and monosaccharides. During the investigation it was found that the microwave hydrolysis process was able to solubilize upto 50% wheat straw biomass by weight, mainly as oligosaccharides though also containing mixtures of pentose, hexose and anhydro-sugars with concentrations of up to 2 g L -1 . However, a fine balance between elevated monosaccharide yields and the production of inhibitive compounds had to be struck with optimal microwave hydrolytic conditions found to be 190 °C. Further testing utilizing several different types of lignocellulosic biomass demonstrated it was possible to attain 65% carbon efficiency in the conversion of Laminaria saccharina to hydrolysis products. The system was scaled to 600 mL using DDGS successfully solubilizing 66% of the feedstock, producing 33 g L -1 hydrolysate. M. pulcherrima grew well on this hydrolysate in a controlled stirred tank bioreactor (2L), yielding 8.38 g L -1 yeast biomass, a yeast biomass coefficient of 0.25. This presents an exciting, feedstock agnostic, pathway to the energy efficient production of a wide variety of commercially valuable chemical products without the need for extensive pre and post processing technologies. Graphical abstract: Image 1